OC-074 A 5- year tertiary centre experience of endoscopic ultrasound guided fine needle aspiration for diagnosis of solid pancreatic mass lesions. (17th June 2017) - Skouras, T; Bonnet, L; Swaminathan, M; Mcgalliard, R; Metussin, A; Evans, J; Sarkar, S; Giles, T; Sheard, J; Cullen, A; Brougham, K; Ramesh, J
Abstract : Introduction: EUS FNA is accepted as the primary modality for tissue diagnosis of solid pancreatic lesions. The presence of on-site cytopathology for immediate evaluation during endoscopic ultrasound-guided fine needle aspiration (EUS FNA) has previously been shown to improve performance characteristics. Due to service pressures EUS FNA is also undertaken in the absence of in-room cytopathology assistance. This is a review of current practice. Method: We retrospectively assessed 700 consecutive EUS-FNA procedures from January 2011 to January 2016. 459 (65.5%) solid pancreatic lesions were included in the final analysis after excluding 230 for biliary strictures, hepatic lesions, lymph nodes, gastric, oesophageal lesions, pancreatic cysts and 11 for insufficient information. Results: In 399 (86.9%) cases on-site cytopathology support was available, while the remaining was unsupported. There were 228 males (57.1%) in the supported and 29 (48.3%) in the unsupported group. Mean age was 64.6(SD: 11.4) and 67.4(SD: 11.9) respectively. The mean number of passes in the two groups were 2.8 (SD: 1.12) and 1.9 (SD: 1.0) (p<0.0001). A conclusive diagnosis (malignant, benign, NET, GIST) was made in 84% (67%, 12%, 5%, 0%) of the supported group and in 38% (23%, 10%, 3%, 2%) of the unsupported (p<0.0001). The mean follow up for the entire cohort was 14.2 months (SD:14.1) and mean survival of in patients diagnosed with malignancy was 10.9 months (SD: 8.7). Overall performance characteristics of EUS FNA were Sensitivity: 90.8% Specificity: 86.9% PPV: 91.8% NPV: 85.4% Conclusion: This review confirms high performance characteristics of EUS FNA. The presence of on-site cytopathologist significantly increases the diagnostic yield. Disclosure of Interest: None Declared